2016
DOI: 10.1007/s00383-016-3877-2
|View full text |Cite
|
Sign up to set email alerts
|

The burden of excluding malrotation in term neonates with bile stained vomiting

Abstract: Increasing awareness of the potential consequences of bilious vomiting appears to have resulted in increased referrals with no increase in detection of malrotation. Prospective studies are required to determine whether investigation of all infants with unexplained bilious vomiting is required and if it is possible to select cases for surgical referral.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 13 publications
4
21
0
Order By: Relevance
“…This may be because we excluded the cases of antenatally detected pathologies but could also be an indication of an increasing likelihood of paediatricians/neonatologists referring cases of bilious vomiting due to the increased awareness of the risks. This is supported by the report from Drewett et al 2 who also found an increase in referrals to their centre without an increase in the detection of malrotaion.…”
Section: Discussionsupporting
confidence: 61%
“…This may be because we excluded the cases of antenatally detected pathologies but could also be an indication of an increasing likelihood of paediatricians/neonatologists referring cases of bilious vomiting due to the increased awareness of the risks. This is supported by the report from Drewett et al 2 who also found an increase in referrals to their centre without an increase in the detection of malrotaion.…”
Section: Discussionsupporting
confidence: 61%
“…Only two infants in our cohort were diagnosed with malrotation, both presenting after 24 hours, which is consistent with other reports in the literature. [7]. Our ndings demonstrated that infants with surgical pathology were more likely to present later.…”
Section: Discussionmentioning
confidence: 61%
“…30% of neonates with malrotation present within 3-7 days, and 80% by 1 month, indicating that many cases will present after discharge from hospital. [7]. One study reported that 15% of term infants less than 7 days old transferred by the London Neonatal Transport Service were for BV.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This wide range of abnormalities leads to various acute and chronic presentations of the disease (1,2). Since this disease is often associated with acute symptoms such as acute midgut volvulus, catastrophic risk of ischemia, and midgut gangrene, it must be considered as a serious surgical emergency and must be immediately diagnosed and the patients should undergo surgery prior to development of midgut gangrene (3).…”
Section: Introductionmentioning
confidence: 99%